Response analysis and control of plates induced by piezoelectric actuators using finite element method - Thien M. Tran; Trieu L. Vo; Son H. Nguyen (Vietnam Journal of Mechanics)
In this article, the shape deformation of the plate bonded to the piezoelectric actuators and sensors is analyzed using the finite element method, and then controlled by an algorithm. It expresses the need to conduct the comparison between non-controllable and controlled ways with low-order finite element methods because of the low cost of investigation. The proposed method is investigated in three cases studied to compare and prove the feasibility and verification. To do these tasks, the effects of coupling between the electric and mechanical properties of piezoelectric materials draw significant attention to the material’s potential applications such as actuators and sensors. Firstly, a rectangular piezoelectric actuator with symmetrically bonded three sensors is considered. The piezoelectric actuator of the injector is implemented in the second experiment. Finally, this study is applied to control the diving board in diving sports. As the simulated results, the deformed shape of piezoelectric actuators can be computed accurately using the finite element method, demonstrating the relation between the central displacement of the piezoelectric actuator in the injector and the voltage level, being linear. An algorithm controls the shape and position of sheet metal to make a foundation and premises for the empirical process and applies it in production.